PENELITIAN DAN PENGEMBANGAN SILABUS BAHASA INGGRIS PROGRAM STUDI PENERBITAN - Suratni Suratni (Jurnal Ilmiah Publipreneur, 2014)
The development of research measures aim to (1) know the current syllabus; (2) get the data and conclusions about the syllabus; (3) find out theoretical syllabus developed nowadays; (4) draft and develop a new syllabus to suit the needs of students, faculty, and industry; (5) get the validity of the test results by getting experts to the syllabus; (6) get the limited field test results against the syllabus; (7) get the eligibility of the syllabus. There are two discussions in this research. First, an examination of the current English syllabus with study documents, learning, observation and analysis of the needs for the development of the syllabus. Second, the language syllabus development has been done by arranging the first prototype. Results of the tests on these students and lecturer next votes disqualified by experts. In this case, all three experts agree that the English syllabus in the third prototype is appropriate and valid to be implemented in PoliMedia.